APEC and financial exclusion: Missed opportunities for collective action? - John Conroy (Asia-Pacific Development Journal, 2006)
The Asia-Pacific Economic Cooperation (APEC) has recently recognized the phenomenon of “financial exclusion” in its member economies, in consequence of a realization of the need to deal with the “losers” in the globalization process. With leadership from Mexico in 2002, APEC considered the merits of “microbanking” as a remedy for financial exclusion. With a number of member economies preferring to deal with financial exclusion as a “development” issue, rather than as a general condition in all APEC economies, APEC appears to have settled upon “microfinance”, rather than microbanking, as the solution to financial exclusion.